Validation of body surface colonic mapping (BSCM) against high resolution colonic manometry for evaluation of colonic motility - Sean H. B. Seo; Cameron I. Wells; Tully Dickson; David Rowbotham; Armen Gharibans; Stefan Calder; Ian Bissett; Greg O’Grady; Jonathan C. Erickson (Scientific Reports, 2024)
Abstract Abnormal cyclic motor pattern (CMP) activity is implicated in colonic dysfunction, but the only tool to evaluate CMP activity, high-resolution colonic manometry (HRCM), remains expensive and not widely accessible. This study aimed to validate body surface colonic mapping (BSCM) through direct correlation with HRCM. Synchronous meal-test recordings were performed in asymptomatic participants with intact colons. A signal processing method for BSCM was developed to detect CMPs. Quantitative temporal analysis was performed comparing the meal responses and motility indices (MI). Spatial heat maps were also compared. Post-study questionnaires evaluated participants’ preference and comfort/distress experienced from either test. 11 participants were recruited and 7 had successful synchronous recordings (5 females/2 males; median age: 50 years [range 38–63]). The best-correlating MI temporal analyses achieved a high degree of agreement (median Pearson correlation coefficient (Rp) value: 0.69; range 0.47–0.77). HRCM and BSCM meal response start and end times (Rp = 0.998 and 0.83; both p < 0.05) and durations (Rp = 0.85; p = 0.03) were similar. Heat maps demonstrated good spatial agreement. BSCM is the first non-invasive method to be validated by demonstrating a direct spatio-temporal correlation to manometry in evaluating colonic motility.